Another Look at Liquidity Preference - Lorie, Henri R. (Quarterly Journal of Economics, 1980)
This paper shows that a "precautionary" demand for money can be derived in models of the state of nature variety with uncertain cash requirements even if sales of assets incur no real costs and investors are risk-neutral. The randomness of asset prices results from uncertainty about the future state of the world that determines cash requirements, hence particular market responses and ultimately equilibrium prices. Positive correlation between the amount of assets to be liquidated and the liquidation price is a sufficient condition for the derivation of an interest-elastic demand for liquidity. The correlation coefficient is a "measure of illiquidity" of a perfectly marketable asset. Interesting comparative static results are also derived.